Aerobic Palladium‐Catalyzed Dioxygenation of Alkenes Enabled by Catalytic Nitrite1. (6th November 2014) - Wickens, Zachary K.; Guzmán, Pablo E.; Grubbs, Robert H.
Abstract Catalytic nitrite was found to enable carbon–oxygen bond‐forming reductive elimination from unstable alkyl palladium intermediates, providing dioxygenated products from alkenes. A variety of functional groups were tolerated, and high yields (up to 94 %) were observed with many substrates, also for a multigram‐scale reaction. Nitrogen dioxide, which could form from nitrite under the reaction conditions, was demonstrated to be a potential intermediate in the catalytic cycle. Furthermore, the reductive elimination event was probed with 18O‐labeling experiments, which demonstrated that both oxygen atoms in the difunctionalized products were derived from one molecule of acetic acid.